2006
DOI: 10.1097/00006231-200608000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear medicine imaging of bone infections

Abstract: The inflammation and infection of bone include a wide range of processes that can result in a reduction of function or in the complete inability of patients. Apart from the inflammation, infection is sustained by pyogenic microorganisms and results mostly in massive destruction of bones and joints. The treatment of osteomyelitis requires long and expensive medical therapies and, sometimes, surgical resection for debridement of necrotic bone or to consolidate or substitute the compromised bones and joints. Radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(65 citation statements)
references
References 118 publications
0
55
1
8
Order By: Relevance
“…In particular, haematopoietically active marrow usually develops around joint prostheses, producing an alteration of the normal distribution of the bone marrow. Furthermore, in peripheral bones, especially after orthopaedic surgery, there are often displacements of bone marrow with "hot spots" that must be distinguished from focal infection (Prandini et al, 2006).…”
Section: Methods and Pitfallsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, haematopoietically active marrow usually develops around joint prostheses, producing an alteration of the normal distribution of the bone marrow. Furthermore, in peripheral bones, especially after orthopaedic surgery, there are often displacements of bone marrow with "hot spots" that must be distinguished from focal infection (Prandini et al, 2006).…”
Section: Methods and Pitfallsmentioning
confidence: 99%
“…It is most sensitive when the prosthesis has been implanted at least 2 to 5 years earlier (for hip and knee, respectively). Bone scintigraphy is largely available with low cost (Prandini et al, 2006). It consists of a dynamic imaging sequence (early phase), called the flow or perfusion phase (first phase), followed immediately by static images of the region of interest, the blood-pool or soft-tissue phase (second phase).…”
mentioning
confidence: 99%
“…Özellikle diz ve kalça protez enfeksiyonlarında ameliyat üzerinden 2 yıldan fazla zaman geçtiyse hassasiyet artmaktadır (25). Uygulama kan akımı veya perfüzyonu gösteren dinamik fazı (ilk faz) takiben ilgi alanına ait kan havuzu veya yumuşak doku fazını gösteren statik görüntüleri (ikinci faz) ve enjeksiyondan 2-4 saat sonra alınan planar statik geç görüntülerden (üçüncü faz) oluşur.…”
Section: Tc-99mi̇şaretlidifosfonatlar(kemiksintigrafisi)unclassified
“…Kemik sintigrafisini yorumlamada, radyofarmasötik tutulum özelliklerindeki değişkenlikler nedeni ile asemptomatik hastalarda ve özellikle diz protezlerinde sorunlar mevcuttur. Buna yönelik bazı araştırmacılar tarafından kantitatif analiz ve yorumlamada yardımcı olabilecek sınıflandırmalar denenmiş, ancak bu sorun çözülememiştir (9,10,25,26). Cerrahi sonrasındaki yıllarda aktivite tutulumları değişik oranlarda devam edebilir.…”
Section: Tc-99mi̇şaretlidifosfonatlar(kemiksintigrafisi)unclassified
“…More recent investigations have shown that macrophages and angiogenic endothelial cells express high levels of monocyte chemoattractant peptide 1, vascular endothelial growth factor (VEGF), and VEGF receptors; these findings suggested that these cell types work with each other to generate and maintain chronic inflammation in a variety of disorders, including bacterial, fungal, and viral infections, rheumatologic and autoimmune disorders, atherosclerosis, organ transplant rejection, and cancer (6)(7)(8). A noninvasive method for assessing the presence, location(s), extent, and intensity of increased VEGF receptor expression would be of clinical value, particularly in chronic joint and soft-tissue infections, which are notoriously difficult to detect with standard markers (such as gallium, 18 F-FDG [with PET], and radiolabeled white blood cells) (9)(10)(11). Serial imaging of VEGF receptor expression could also be quite helpful in guiding biologic modifier therapy for common chronic noninfectious inflammatory disorders (such as rheumatoid arthritis, inflammatory bowel disease, and multiple sclerosis), for which annual drug costs alone can be as high as $10,000-$50,000 (12)(13)(14).…”
mentioning
confidence: 99%